The Interpretive Shift in Argentine Private Law: From Legality to Conventionality. An Analysis Based on a Constitutional Ruling - Martínez, Rubén (2025)
This article analyzes the interpretative change in Argentine private law resulting from the process of constitutionalization of law, focusing on the ruling of the Supreme Court of Justice of the Nation in the case “Institutos Médicos Antártida s/ quiebra” (bankruptcy proceedings). This case presents the intersection between bankruptcy law, constitutional law, and international human rights law, highlighting the application of conventionality control and the protection of creditors in situations of extreme vulnerability. Breaking with a traditional legalistic interpretation, the Court declared the bankruptcy privilege regime regulated by the insolvency law unconstitutional, granting a disabled minor the recognition of a special priority privilege in the claim verification process. This ruling examines how a provision of private insolvency law is reinterpreted in light of constitutional principles and international treaties. Finally, the article reflects on the need for legislative reform to incorporate these jurisprudential advances into the Argentine bankruptcy regime.